Penerapan Afirmasi Positif Untuk Menurunkan Tingkat Nyeri Dismenorea Remaja Putri - Shinta Wahyusari; Rizka Yunita (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Female adolescent is very susceptible in experiencing dysmenorrhea on every mentrual period. This condition can cause discomfort and pain around the stage so that it can hinder daily activities. Community service activities are carried out to train female adolescent to do positive affirmations as an alternative therapy in reducing dysmenorrhea pain levels. There are several stages carried out to achieve the activity target including the preparation stage, the introduction stage, the implementation stage and the monitoring evaluation stage. First is conducting a preliminary study to identify the problems experienced by female adolescent and prepare all the necessary activity instruments. The next process is explaining the aims and objectives to partners and carrying out and giving informed consent. Then the implementation phase includes conducting an assessment of the level of dysmenorrhea pain experienced by female adolescent. After that, health education about dysmenorrhea was given to female adolescent. Furthermore, training female adolescent to do positive affirmations as one of the nursing therapies that can be done to reduce the level of dysmenorrhea pain. In the final stage, the monitoring and evaluation process is carried out in the following month. Monitoring and evaluation activities are carried out by reassessing the level of dysmenorrheal pain in female adolescent during their next menstrual period. From the results of monitoring and evaluation activities, it was found that most young women experienced a decrease in dysmenorrheal pain levels after carrying out positive affirmations and female adolescent were able to carry out positive affirmations independently.